2000
DOI: 10.1046/j.1365-2672.2000.01147.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a Lactobacillus amylovorus mutant depleted in conjugated bile salt hydrolase activity: relation between activity and bile salt resistance

Abstract: . 2000. Growth experiments were conducted on Lactobacillus amylovorus DN-112 053 in batch culture, with or without pH regulation. Conjugated bile salt hydrolase (CBSH) activity was examined as a function of culture growth. The CBSH activity increased during growth but its course depended on bile salts type and culture conditions. A Lact. amylovorus mutant was isolated from the wild-type strain of Lact. amylovorus DN-112 053 after mutagenesis with N-methyl-N H -nitro-N-nitrosoguanidine. An agar plate assay was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 35 publications
2
56
1
Order By: Relevance
“…BSH mutant strains of Lactobacillus amylovorus, 44 and Listeria monocytogenes 45,46 were shown to be significantly more sensitive to conjugated bile salts than their wild-type counterparts. Indeed, glycine-conjugated BA was found to be significantly more inhibitory than taurine-conjugates, particularly at low environmental pH.…”
Section: A Microbial View Of Bile Salt Hydrolysismentioning
confidence: 98%
“…BSH mutant strains of Lactobacillus amylovorus, 44 and Listeria monocytogenes 45,46 were shown to be significantly more sensitive to conjugated bile salts than their wild-type counterparts. Indeed, glycine-conjugated BA was found to be significantly more inhibitory than taurine-conjugates, particularly at low environmental pH.…”
Section: A Microbial View Of Bile Salt Hydrolysismentioning
confidence: 98%
“…The presence of a functional BSH results in the intracellular accumulation of free bile acids, which become protonated in a stoichiometric manner, decreasing energydependent H 1 -ATPase-driven proton efflux. BSHs from human intestinal lactobacilli generally have higher affinity for glycine conjugates (26)(27)(28)(29). This observation may lend weight to the hypothesis of De Smet et al (26), or the higher affinity of BSHs for glycine conjugates may have evolved because glycine conjugates are generally higher in proportion (3:1) than taurine conjugates in human bile (6).…”
Section: Benefits Of Bshs To the Bacteriummentioning
confidence: 82%
“…Disruption and deletion of bsh in lactobacilli caused loss of corresponding activity against tauro/glyco-CBA (34,40). The resistance of bsh mutants of Lactobacillus amylovorus and Lactobacillus plantarum to bile acids/salts was reduced compared to the respective wild-type strains (13,16,24). However, no convincing in vivo experiments have so far demonstrated that bsh contributes to bile resistance in these or other probiotic bacteria.…”
mentioning
confidence: 99%
“…However, there is also evidence that the production levels and enzymatic activity of Bsh are not directly related to overall bile resistance levels (24,41). In addition to bsh, other genes (pva and btlB) and the sigma factor B have been shown to contribute to bile resistance in L. monocytogenes EGDe (3).…”
mentioning
confidence: 99%